O USO DO BIM EM PROJETOS ELÉTRICOS E SOLARES FOTOVOLTAICOS, NA CONSTRUÇÃO CIVIL - BRUNO DA SILVA OLIVEIRA (2020)
Sustainable development is becoming more and more present in society, reaching different market segments and intensifying efforts for smarter information management systems relevant to the various fields of human performance. Within this reality, the initiative of BIM emerges that promotes the insertion of information in the design of the building, bringing results from the planning of the envelope, to the management of its facilities. It is in this context that the electrical installations and technologies of emerging energy generation, being the focus of this study the solar photovoltaic energy, should be inserted, aiming to attend to the concept of integrated project, which stands out in the civil construction market, bringing minor problems of incompatibility, better management of work stages, accurate budgeting, and decision making consistent with sustainable demands. In the search for integrating electrical installations and photovoltaic solar generation to BIM, this study seeks to raise the technical barriers related to the theme, understanding which technologies can be involved and which mechanisms and work procedures for the interoperability of the themes within of an integrated BIM model, with the following objectives: Presenting existing technologies, demonstrating the means of exchanging information between electrical and solar projects through BIM, presenting the work processes for integration between different design modalities, in addition to identifying the technological and procedural barriers faced for the integration of solar photovoltaic and electrical projects to BIM, in civil construction, proposing solutions. The platforms and their main operating characteristics were presented, as well as work flows and ending with the application in small and large buildings, thus demonstrating that there are possible work structures that meet the BIM and technical demands for photovoltaic and electrical solar projects.